Morphology of the eggs of the genus Belminus (Hemiptera: Reduviidae: Triatominae) by optical and scanning electron microscopy - Sandova, Claudia M.; Nieves, Elsa; Angulo, Victor M.; Da Rosa, Joao Aristeu [UNESP]; Aldana, Elis (Magnolia Press, 2011)
The external morphology of eggs of the species Belminus corredori Galvao & Angulo, 2006, Belminus herreri Lent & Wygodzinsky, 1979 and Belminus ferroae Sandoval, Pabon, Jurberg & Galvao, 2007 is described for the first time using scanning electron microscopy (SEM). Females lay one egg at a time; the shape of the egg is oval with lateral flattening, a rounded caudal area and a true and simple convex operculum. The average size of the egg among these species is 0.51-0.58 mm in length and 0.36-0.4 mm in width. As a generic character we highlight the discovery of a chorion rim with one to four grooves always joined to the micropyles. All species present a clear polygonal pattern only in the operculum and in the egg's cephalic region, while the median and caudal regions show a smooth appearance, features that are shared only with the eggs of the genus Alberprosenia. A discriminant analysis of the polygonal design of the operculum proved to be useful for the identification of the species.
Keywords: chorion sculpturing; polygonal cells; operculum; eggshell; SEM